Environmental bisphenol A exposure triggers trained immunity-related pathways in monocytes - Dallio, Marcello; Ventriglia, Lorenzo; Romeo, Mario; Scognamiglio, Flavia; Diano, Nadia; Moggio, Martina; Cipullo, Marina; Coppola, Annachiara; Ziogas, Athanasios; Netea, Mihai G.; Federico, Alessandro (Frontiers in Immunology, 2023)
Trained Immunity represents a novel revolutionary concept of the immunological response involving innate immune cells. Bisphenol A is a well-known endocrine disrupter, widely disseminated worldwide and accumulated in the human body. Due to the increased interest regarding the effects of plastic-derived compounds on the immune system, our purpose was to explore whether BPA was able to induce trained immunity in human primary monocytes in vitro using low environmental concentrations. Materials and methods: We extracted BPA from the serum of 10 healthy individuals through a liquidliquid extraction followed by a solid phase extraction and measured the concentration using an HPLC system coupled to a triple quadrupole mass spectrometer. In parallel, monocytes were isolated from whole blood and acutely stimulated or trained with BPA at three different concentrations (1 nM, 10 nM, 20 nM). Pro-and anti-inflammatory cytokines (IL-1β, TNF-α, IL-6, and IL-10) production were assessed after 24 hours of acute stimulation and after Lipopolysaccharide (LPS) rechallenge. A comprehensive overview of the metabolic changes after BPA acute stimulation and trained immunity induction was assessed through extracellular lactate measurements, Seahorse XFb metabolic flux analysis and ROS production. Results: Monocytes primed with BPA showed increased pro-and anti-inflammatory cytokine responses upon restimulation, sustained by the modulation of the immunometabolic circuits. Moreover, we proved the non-toxic effect of BPA at each experimental concentration by performing an MTT assay. Additionally, correlation analysis were performed between pro-and anti-inflammatory This is a provisional file, not the final typeset article cytokines production after LPS acute stimulation or BPA-mediated trained immunity and BPA serum concentrations showing a significant association between TNF-α and BPA circulating levels. Discussion: Overall, this study pointed out for the first time the immunological effects of an environmental chemical and plastic-derived compound in the induction of trained immunity in a healthy cohort.